The Kind Care Bundle: A Curriculum to Teach Medical Students the Behaviors of Kind, Compassionate Care - Cynthia M. Cooper; Galina Gheihman (Association of American Medical Colleges, 2021)
Introduction Patients' hospital experiences can be adversely affected by clinicians' negative behaviors. Simple positive behaviors, however, can have a dramatic impact on patient-clinician relationships. Medical students starting clinical training are ideal educational targets for learning good behavioral habits that promote kind, compassionate care. Methods We developed the Kind Care Bundle, a collection of concrete verbal and nonverbal behaviors for showing compassion in patient interactions. The curriculum was taught in 3-hour small-group interactive sessions to first-year students. Students reflected on personal experiences of compassionate care and role-played the use of the Kind Care Bundle. In pairs, students interviewed patients about their experiences of kind, compassionate care while practicing the Kind Care Bundle. Students completed a postsession evaluation with Likert scales and free-text responses. Results Thirty-seven of 40 students (92%) completed postsession evaluation forms. Session organization was considered excellent (27 of 37 students, 73%) or very good (nine of 37, 27%). Session relevance was rated as excellent by 30 of 37 students (81%) and very good by six of 37 students (16%). Students believed the bundle filled an educational gap. Qualitative themes included appreciation of concrete behaviors in the bundle, importance of empathy, and opportunity to reflect on one's own experience of compassion. Discussion Students appreciated learning about specific behaviors for improving patient interactions. Targeting preclinical medical students has the potential to promote kinder and more compassionate patient interactions during subsequent clinical training. The long-term impact on students' behavior and on their personal and professional development requires further study.